Access to public information: Evaluation of the transparency portal of the executive branch of Santa Catarina - Knoll , Alessandra; Cademartori , Luiz Henrique; Milchert, Rodrigo de Oliveira (Seven Editora, 2023)
This paper sought to analyze the fulfillment of the disclosure of public financial statements of  the government on the Executive Branch of Santa Catarina Transparency Portal, conceptualize  transparency, public revenue and public expenses, present the legal framework relevant to the  subject and verify whether the state transparency website is in line with the requirements on the  matter. The data and information of the financial statements of the state on the most searched  topics on the portal and those that are required by regulatory authorities was presented. The  evaluation was based on the Transparent Brazil Scale developed by the Brazilian Office of the  Comptroller General (CGU), which examines, according to some parameters, the official  websites of the Brazilian federative entities. After carrying out the research, it was concluded  that there are difficulties in locating and checking relevant data by individuals due to the need  to have a minimum of expertise and skills when evaluating what is presented on the website.  The elaboration of a document with instructions on how to analyze the government data to  improve education and accountability of the public administration is suggested.  DOI:https://doi.org/10.56238/sevened2023.006-096